Phase angle analysis for PWM-switched autotransformer voltage-sag compensator - Mansor M.; Rahim N.A. (2023)
This study proposes a controller for a single- and a three-phase pulse width modulation (PWM) voltage sag compensator. The controller comprises a combination of a new sag detection technique namely phase angle analysis and a PWM voltage controller. The detection technique offers immediate voltage sag detection and compensation even with the presence of phase jump and harmonic content in the input voltage. The controller is then used to control a proposed singlephase and a three-phase voltage sag compensator. The proposed compensator's topology is able to reduce current stress in the switches and able to avoid non-stop operation during sag events. It also plays a role in assisting the system to avoid delay in compensating output voltage. The two systems are designed using MATLAB/Simulink simulation software and verified by a laboratory prototype with a TMS320F2812 as the main controller. Simulation and experimental results are provided to validate the system performance. The Institution of Engineering and Technology 2012.